Long-Term Outcome after Dynamic Graciloplasty for Treatment of Persistent Fecal Incontinence in Patients with Anorectal Malformations - Danielson, Johan; Karlbom, Urban; Wester, Tomas; Graf, Wilhelm (European Journal of Pediatric Surgery, 2019)
Purpose Dynamic graciloplasty (DGP) has been used to treat severe fecal incontinence since the 1980s. Previous studies have shown an inferior outcome in patients with anorectal malformations (ARMs). Our experience has been that DGP has been appreciated by ARM -patients. The objective of the study was to evaluate the long-term outcome of DGP in our patients with ARM compared with patients with other underlying conditions.Materials and Methods Twenty-three patients operated with DGP at our institution from 1996 to 2010 were sent validated bowel function and quality of life questionnaires. Eighteen of 23 responded. Seven had ARM and 11 had other etiologies of fecal incontinence. The mean follow-up time was 11.6 years (range, 5–17).Results Four of 7 of the patients with ARM and 8 of 11 of patients with other etiologies used their implants at follow-up. The Miller incontinence score was slightly higher for patients with ARMs, but they had less constipation and higher Fecal Incontinence Quality of Life (FIQL)- and 36-Item Short Form Health Survey (SF-36) scores. None of the differences were statistically significant.Conclusion This study cannot confirm earlier reports in which DGP has an inferior outcome in patients with ARM. We therefore believe that the procedure should remain a treatment option for selected patients.
Keywords: anorectal malformation; fecal incontinence; dynamic graciloplasty; long-term outcome